Moderate Muslims’ Views on Multicultural Education, Freedom of Expression, and Social Media Hate Speech: An Empirical Study in West Java Indonesia - Husni, Husni (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2019)
West Java Province is often assumed to be the center of radical Islam growth in Indonesia, especially since the reform era. The truth and validity of this presumption need to be proven empirically. Indeed, in this province, there are a number of hardline Islamic organizations with the members spread in almost all corners of West Java. The Wahid Foundation survey from 2010 to 2017 always put this province with the highest incidence of religious-based violence. Therefore, the study on the views of moderate Muslim leaders on freedom of expression, hate speech on social media, and the importance of multicultural education are deemed to be very necessary. The qualitative research data on 73 moderate Muslim figures in West Java was collected by direct interviews, via email, social media, telephone calls, and from their opinions in various media. The results showed that moderate Muslim leaders in West Java uphold and respect freedom of expression as one of the basic human rights, but they refuse if this right is misused to spread hate speech. They also agree with the importance of rules and law enforcement to overcome the problem of spreading hate speech, but according to them, the legal aspect is not the only approach. They view multicultural education as a long-term strategy to build a mature democratic society with high ethical standards.